OP36 Decisions about smoking in patients screened with the early cdt-lung test for the early detection of lung cancer: a qualitative study - Young, Ben; Vedhara, Kavita; Robertson, John; das Nair, Roshan (BMJ Publishing Group, 2017)
Background: Routine screening for lung cancer in high risk groups (characterised by age and smoking history) is recommended in the USA and may be implemented elsewhere. It is unclear whether being screened for lung cancer promotes smoking cessation or conversely provides false reassurance and a ‘license to smoke’. This study aimed to understand how experiences of lung cancer screening influence individual decision making about smoking.